Mendukung konservasi penyu di Pantai Distrik Manokwari Utara melalui program KKN-PPM: Supporting turtle conservation on the Beaches of North Manokwari District Through the KKN-PPM program - Boli, Paulus; Purba, Gandi Y. S.; Allo, Alberto (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT The problem faced by the society of Mubraidiba Village for a long time has been catching turtles. The caught turtles are used for the family's protein needs and some are sold as family income and are also preserved to be used as wall decorations. This has resulted in the number of turtles decreasing over time. The purpose of the KKN-PPM program is to implement the knowledge that students have in carrying out turtle conservation together with the Manduni Putra Joint Business Group and the community of Mubraidiba village on the coast of North Manokwari District. Implementation of this activity consists of 1) potential mapping and problem identification; 2) preparation of program and activity plans; and 3) program socialization. The program will be implemented for two months (19 June -15 August 2020). The results of the monitoring did not find any turtles landing on Astelin Beach, Mubraidiba Village, so activities continued on Muara Prafi Beach, where quite a lot of turtles were still landing because the environmental conditions were still natural. Egg transfer activities were carried out twice on July 20 and July 22, 2020, with 114 green turtles and 102 olive ridley turtles. Hatching success was 94.2% and hatchling rearing success was 78.4%. The number of hatchlings released into the sea was 80, this activity was a form of outreach to the community of Mubraidiba Village and surrounding villages. Keywords: Turtle Conservation; Mubraidiba Village; Community Outreach; Egg Relocation; KKN-PPM ABSTRAK Permasalahan yang dihadapi masyarakat Kampung Mubraidiba sejak dahulu telah melakukan penangkapan penyu. Penyu yang ditangkap dimanfaatkan untuk kebutuhan protein keluarga dan sebagian dijual sebagai pendapatan keluarga dan juga diawetkan untuk dijadikan hiasan dinding. Hal ini mengakibatkan jumlah penyu mengalami penurunan dari waktu ke waktu. Tujuan program KKN-PPM adalah mengimplementasikan pengetahuan yang dimiliki mahasiswa melakukan konservasi penyu bersama dengan Kelompok Usaha Bersama (KUB) Manduni Putra dan masyarakat Kampung Mubraidiba di pesisir pantai Distrik Manokwari Utara. Pelaksanaan kegiatan ini terdiri dari: 1) pemetaan potensi dan identifikasi masalah; 2) penyusunan rencana program dan kegiatan; 3) sosialisasi program. Pelaksanaan program selama dua bulan (19 Juni -15 Agustus 2020). Hasil monitoring tidak menjumpai penyu yang mendarat di Pantai Astelin Kampung Mubraidiba, sehingga kegiatan dilanjutkan di Pantai Muara Prafi yang masih cukup banyak penyu yang mendarat karena kondisi lingkungan masih alami. Kegiatan pemindahan telur dilakukan 2 kali tanggal 20 Juli dan 22 Juli 2020, penyu hijau sebanyak 114 butir dan penyu lekang 102 butir. Sukses penetesan sebesar 94,2% dan sukses pemeliharaan tukik 78,4%. Jumlah tukik yang dilepas liarkan ke laut sebanyak 80 ekor, kegiatan ini sebagai bentuk sosialisasi kepada masyarakat Kampung Mubraidiba dan kampung sekitarnya. Kata kunci: Konservasi Penyu; Kampung Mubraidiba; Penyuluhan Masyarakat; Pemindahan Telur; KKN-PPM